Il Fast-Track delle fratture di femore prossimale over 65: analisi dell’epicrisi e sviluppo di modelli organizzativi efficaci - Calori, G.M.; Colombo, M.; Campi, A.; Di Maggio, B.; Caiaffa, V.; Momoli, A.; Caroli, F.; Longo, G.; Donelli, F.; andelli, F.; De Simoni, P.; Pellegrino, A.; et al. (Lo Scalpello - Journal, 2018)
FAST-TRACK OF PROXIMAL FEMUR FRACTURES IN PATIENTS OVER 65 YEARS: ANALYSIS OF THE EPICRISIS AND DEVELOPMENT OF EFFECTIVE ORGANIZATIONAL MODELS During the Trauma Meeting 2017 in Riccione an important Round Table took place entitled “Analysis of the epicrisis and development of effective organizational models” within the session “Fast-track of proximal femur fractures in patients over 65 years”. Given the great relevance of the topic and the precious contribution of the participants, it was decided to create the following scientific manuscript of Discussion and Consensus, which contains the answers to the five questions that were the subject of the Round Table.